2013
DOI: 10.4103/0019-5154.105280
|View full text |Cite
|
Sign up to set email alerts
|

Direct immunofluorescence in cutaneous vasculitis: Experience from a referral hospital in India

Abstract: Background:Cutaneous vasculitis is commonly recognized and biopsied, owing to ease of access. Most biopsies are also subjected to direct immunofluorescence (DIF), though the rates of positivity vary. This is an attempt to assess the utility of DIF and glean data that will help optimize the test.Objective:To assess the diagnostic utility of DIF in cutaneous vasculitis.Materials and Methods:All cases of suspected cutaneous vasculitis submitted for DIF between 2004 and 2010 were included. Clinical data, histopath… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
20
0
7

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(30 citation statements)
references
References 16 publications
3
20
0
7
Order By: Relevance
“…9,10 A causal agent or an underlying condition has been reported in 20-85 percent of the cases. 11,12,10,13 Similar to our findings, a previous study from India had found that drugs were the most common aetiological factor in vasculitis. 14 In contrast to our study, some previous studies had shown that antibiotics rather than NSAIDs were responsible for drug-induced vasculitis.…”
Section: Discussionsupporting
confidence: 88%
“…9,10 A causal agent or an underlying condition has been reported in 20-85 percent of the cases. 11,12,10,13 Similar to our findings, a previous study from India had found that drugs were the most common aetiological factor in vasculitis. 14 In contrast to our study, some previous studies had shown that antibiotics rather than NSAIDs were responsible for drug-induced vasculitis.…”
Section: Discussionsupporting
confidence: 88%
“…DIF microscopy of the lesional skin shows the deposition of immune complexes along the vessel wall, which is of great importance in Henoch‐Schönlein purpura/IgA vasculitis. DIF positivity has been reported to range between 39% and 92% in a few studies conducted on cutaneous vasculitis specimens . Several factors affect the DIF results in vasculitis, including the age of the biopsied lesion and drug intake after the onset of lesions .…”
Section: Discussionmentioning
confidence: 99%
“…DIF positivity has been reported to range between 39% and 92% in a few studies conducted on cutaneous vasculitis specimens . Several factors affect the DIF results in vasculitis, including the age of the biopsied lesion and drug intake after the onset of lesions . Moreover, a nonspecific DIF positivity has been reported in biopsy specimens from the lower legs in patients without vasculitis .…”
Section: Discussionmentioning
confidence: 99%
“…Daha önce bazı merkezlerde yapılan çalışmalarda, İD'lerden en az bir tanesinin bulunması pozitif kabul edildiğinde, kutanöz vaskülitlerde ve LKV'lerde değişken oranlarda (%20-%70,5) DİF pozitifliği bildirildi (6,8,(9)(10)(11)17). Tüm KV'ler için en düşük oran %20 ile Feasel ve arkadaşlarının geniş vaka serisi içeren (1318 vaka) çalışmasında tespit edilirken (6), en yüksek oran Guerraro ve arkadaşlarının 20 vaka analizinde %70 olarak tespit edilmiştir (17).…”
Section: Discussionunclassified
“…Lökositoklastik değişiklikler (nötrofil parçalanmaları ve nükleer kırıntılar) genellikle mevcuttur (5). Vaskülitlerde damar duvarında immunglobülinler (Ig) veya komplemanlardan (C) oluşan immun depozitler (İD) birikebilir ancak birikmeyen vakalar da mevcuttur Literatürde KV'lerden en çok lökositoklastik vakülitler (LKV) ve henoch schonlein purpurası vaskülitlerinde (HSP) yüksek birikim oranları bildirilmiştir (6,8). Bu çalışmada, histopatolojik ve klinik olarak vaskülit tanısı alan, lökositoklastik değişiklikler içeren ya da içermeyen, küçük damarları etkileyen KV (KKV) vakalarını guruplandı-…”
Section: Introductionunclassified